Novel Amphiphilic Biopolymer-Hydrogel as Time-Temperature Sensor - Saruchi (My University, 2017)
Temperature is an important factor affects the quality and safety of various food products. Thus, it is very crucial to control the temperature during both distribution and storage of food products. An intelligent and biodegradable time/temperature indicator (TTIs) was developed which was based on microbial extracellular amphiphilic biopolymer-hydrogel (EAB). TTIs constitute an important part of responsive packaging; they are cost-effective and user-friendly devices to monitor, record, and translate the overall effect of temperature history on food quality in the chill chain down to a product unit level. In the present work, ten bacterial strains were screened for the production ability of extracellular amphiphilic biopolymer (EAB) based on variety of tests like; CTAB (cetyltrimethylammonium bromide) agar plate method, BATH (bacterial adhesion to hydrocarbon), Emulsification stability (E24) test, Drop collapse test and Hemolytic test. Four bacterial strains with higher E24 activity were selected but only one bacterial strain with 61.5% emulsification activity was finally used for the EAB production. Higher EAB production of 0.248 g/l was achieved in EAB media. EAB was further characterized by Scanning electron micrograph (SEM); Fourier transforms infrared spectroscopy (FTIR) and X-ray diffraction (XRD). Furthermore, hydrogel (polyvinyl alcohol (PVA), PVA/chitosan and PVA/EAB) was synthesed using glutaraldehyde (GA) as a cross- linker. Then characterized using SEM, XRD, FTIR and swelling behaviour. Then the TTI (timetemperature indicator) sensor was prepared with all the three different hydrogel and was activated with lactic acid by keeping at 37oC and 4oC. The results of TTI conducted at 40C and 370C for 24 hours indicated the change in the colour of PVA, PVA/chitosan and PVA/EAB-SA1 as yellow to red, yellow to dark brown and yellow to light red respectively. The result of the study this EAB/PVA-hydrogel has possible application in the food industry.
Keywords: Amphiphilic biopolymer; hydrogel; time-temperature indicator; emulsification; hydrocarbons; hydrophilic; hydrophobic; biopolymers